The dynamics of a terrorist targeting process : Anders B. Breivik and the 22 July attacks in Norway /: Anders B. Breivik and the 22 July attacks in Norway. (2016) - Hemmingby, Cato, 1968-; Bjørgo, Tore
No abstract available